Store choice: How understanding consumer choice of 'where' to shop may assist the small retailer. (March 2015) - Goodman, Steve; Remaud, Hervé
Abstract: Recent decades has seen continued rationalization in the retail sector and the growth of 'big-box' or 'category-killer' store formats leaving the small business struggling to compete and at a loss to determine how it can 'win'. We propose that a segment of shopper exists that shop at small businesses for specific reasons. Using a choice experiment approach to investigate the reason consumers choose where to shop amongst small, independent and large scale retailers we see this different segment of consumers appear. Best:worse is a choice method that forces choice amongst a range of variables, designed to uncover 'actual' reasons for decisions made. This paper finds consumer choice for retail stores types identifies a segment that may assist in the sustainability of smaller stores if they cater to the attributes their target consumers seek. This is a contribution to small business researchers and small business strategy and practitioner effort in the marketing and design of small retailer offering. Highlights: Store choice influence better segments the market than traditional demographics. Reasons for store choice identify the three types of store format. Retailers can match their offer with their target markets choice influencers. Rise in large store format is not necessarily the end of small retail.